Chemical biology approaches for studying posttranslational modifications. Issue 4 (4th May 2018) - Yang, Aerin; Cho, Kyukwang; Park, Hee-Sung
ABSTRACT: Posttranslational modification (PTM) is a key mechanism for regulating diverse protein functions, and thus critically affects many essential biological processes. Critical for systematic study of the effects of PTMs is the ability to obtain recombinant proteins with defined and homogenous modifications. To this end, various synthetic and chemical biology approaches, including genetic code expansion and protein chemical modification methods, have been developed. These methods have proven effective for generating site-specific authentic modifications or structural mimics, and have demonstrated their value for in vitro and in vivo functional studies of diverse PTMs. This review will discuss recent advances in chemical biology strategies and their application to various PTM studies.